2015
DOI: 10.1155/2015/973597
|View full text |Cite
|
Sign up to set email alerts
|

Stability Assessment of Candidate Reference Genes in Urine Sediment of Prostate Cancer Patients for miRNA Applications

Abstract: We aimed at assessing the stability of candidate reference genes in urine sediments of men subjected to digital rectal examination for suspected prostate cancer (PCa). Two microRNAs (miR-191 and miR-25) and 1 small nucleolar RNA (SNORD48) were assayed in 35 post-DRE urine sediments of men with PCa and in 26 subjects with histologically confirmed benign prostatic hyperplasia (BPH). The stability of candidate reference genes was assessed through BestKeeper algorithm and equivalence test. miR-200b and miR-452 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 44 publications
1
34
0
2
Order By: Relevance
“…It has been demonstrated that miRNAs are detectable in urine of PCa patients collected after DRE (digital rectal examination) 13 , 14 . As demonstrated in our last study quantitative real-time PCR (qPCR) miRNA analysis could be considered a non-invasive promising tool for diagnostic testing on PCa, and on its prognostic status 15 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that miRNAs are detectable in urine of PCa patients collected after DRE (digital rectal examination) 13 , 14 . As demonstrated in our last study quantitative real-time PCR (qPCR) miRNA analysis could be considered a non-invasive promising tool for diagnostic testing on PCa, and on its prognostic status 15 .…”
Section: Introductionmentioning
confidence: 99%
“…The progressive confirmation of their key role in cancer, their stability in biological fluids and their resistance to various storage conditions69 make miRNAs excellent candidates for the development of minimally invasive biomarkers for cancer diagnosis and prognosis. Unfortunately, a universally accepted procedure to deal with miRNAs does not exist, and data normalization is currently performed through the experimental assessment of candidate housekeeping genes 10. This study was aimed at characterizing a panel of circulating miRNAs that could distinguish PCa from benign prostatic hyperplasia (BPH) in a population of age-matched patients with increased PSA levels.…”
Section: Introductionmentioning
confidence: 99%
“…They also cause changes in gene expression, which can be accurately and sensitively measured by qRT-PCR [17, 20]. This technique normalizes the gene of interest against an endogenous control whose expression remains unaltered in the samples under analysis [21]. The concept of validating reference genes used for normalization in qRT-PCR analysis before use was initially suggested in 2002 [22], and has been realized in various scientific disciplines such as plant sciences [23, 24], cancer [25, 26], stem cells [27, 28], and cardiovascular research [14, 29, 30].…”
Section: Discussionmentioning
confidence: 99%